The Science and Regulation of Food from Genetically Engineered Animals - Eenennaam, Alison L. Van; Hallerman, Eric M.; Muir, William M. (Council for Agricultural Science and Technology (CAST), 2011)
Humans and animals have been consuming genetically engineered (GE) food from plants for decades, but the recent approval of GE salmon intended as human food has resulted in debate and some controversy. Many still have concerns about the environmental impact and food safety issues of such an approval. More research is needed as policymakers struggle with laws ranging from the approval of GE procedures to the labeling of such food in the markets. This Commentary looks at how GE animals are currently regulated and what type of data is needed to demonstrate the safety of GE organisms. The authors also look at the opportunities for public participation in the regulatory process and the implications for the future of this technology.